2017
DOI: 10.1177/0956797617696312
|View full text |Cite
|
Sign up to set email alerts
|

Cruel to Be Kind: Factors Underlying Altruistic Efforts to Worsen Another Person’s Mood

Abstract: When aiming to improve another person's long-term well-being, people may choose to induce a negative emotion in that person in the short term. We labeled this form of agent-target interpersonal emotion regulation altruistic affect worsening and hypothesized that it may happen when three conditions are met: (a) The agent experiences empathic concern for the target of the affect-worsening process, (b) the negative emotion to be induced helps the target achieve a goal (e.g., anger for confrontation or fear for av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 27 publications
6
58
1
Order By: Relevance
“…As well as providing insight into why people regulate others’ emotions, a further contribution of the present research is to highlight a possible alternative account of why people regulate their own emotions. Combining the insights here with those from existing research (e.g., López‐Pérez et al, ; Netzer et al, ; Tamir & Ford, ) suggests that people might regulate their own and others’ emotions motivated by instrumental concerns and that people might also regulate others’ emotions motivated by prosocial concerns. An additional possibility, therefore, is that people might also regulate their own feelings prosocially.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As well as providing insight into why people regulate others’ emotions, a further contribution of the present research is to highlight a possible alternative account of why people regulate their own emotions. Combining the insights here with those from existing research (e.g., López‐Pérez et al, ; Netzer et al, ; Tamir & Ford, ) suggests that people might regulate their own and others’ emotions motivated by instrumental concerns and that people might also regulate others’ emotions motivated by prosocial concerns. An additional possibility, therefore, is that people might also regulate their own feelings prosocially.…”
Section: Discussionsupporting
confidence: 61%
“…This idea is consistent with various theories which posit that people act to benefit others’ goal pursuit in a prosocial or altruistic manner, because this facilitates the formation and maintenance of social relationships and promotes cooperation (e.g., Batson, ; Finkel & Rusbult, ; Grant, ). In line with this possibility, a recent study by López‐Pérez et al () demonstrated evidence that when primed to take the perspective of others, people selected stimuli intended to induce emotions in others that would benefit those others’ performance.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure illustrates the relationship between first‐order valuation system and the second‐order valuation system. The input to the second‐order valuation system can either be one's own emotions (i.e., intrinsic ER) or another person's emotions (i.e., extrinsic ER; Gross, ; López‐Pérez, Howells, & Gummerum, ; Netzer, Van Kleef, & Tamir, ; Zaki & Williams, ). ER occurs once an emotion (W) is perceived (P), a person evaluates whether to regulate (V), and there is a resulting action impulse (A) to regulate.…”
Section: A Process Model Perspectivementioning
confidence: 99%
“…However, the true story is likely to be more complex: not all attempts to improve others' emotions receive positive reactions (e.g., humour often backfires; Williams & Emich, 2014), and people may respond less negatively to some attempts to worsen their feelings (e.g., when people are 'cruel to be kind'; L opez-P erez, Howells, & Gummerum, 2017). Here, we contribute a more nuanced understanding by arguing that the motives that underlie IER influence how others respond to IER (Niven, 2016).…”
mentioning
confidence: 99%